2018
DOI: 10.1111/nhs.12399
|View full text |Cite
|
Sign up to set email alerts
|

Walk the talk: Leader behavior in parental education groups

Abstract: Expectant and new parents are offered parental education groups as a way to support their transition to parenthood. Group leadership in these groups has been found to be challenging. Using a qualitative and summative design, the aim of the present study was to investigate how health professionals describe their role in parental education groups compared to their actual behavior. Thirteen health professional leaders in antenatal and child health services were interviewed. These descriptions were compared with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 23 publications
1
13
0
3
Order By: Relevance
“…In this role, he also strove to The findings of this study suggest that the discussion leader role may be crucial in promoting the goals of PE groups. This finding is consistent with those of a previous study of PE groups, which found that when group leaders take on the role of experts and give lectures, parents have little room to actively participate and interact (Berlin et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In this role, he also strove to The findings of this study suggest that the discussion leader role may be crucial in promoting the goals of PE groups. This finding is consistent with those of a previous study of PE groups, which found that when group leaders take on the role of experts and give lectures, parents have little room to actively participate and interact (Berlin et al, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, the role that the group leader chooses to assume for example, discussion leader or expertmay be of equal or greater importance (Berlin et al, 2018). Studies comparing fatherhood groups led by men and women could help resolve this question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have highlighted the opportunities for PE groups to give strength to parents in their parenting (Ahldén, Göransson, Josefsson, & Alehagen, 2012; Asenhed et al., 2014; Barimani et al., 2017; Berlin, Törnqvist, & Barimani, 2016; Schrader McMillan, Barlow, & Redshaw, 2009; Svensson, Barclay, & Cooke, 2009). However, group leaders express feelings that they do not have enough pedagogical knowledge to lead PE groups (Barlow, Redshaw, & Underdown, 2009; Berlin, Rosander, Forslund Frykedal, & Barimani, 2018; Forslund Frykedal, Barimani, Rosander, & Berlin, 2019; Forslund Frykedal, Rosander, Berlin, & Barimani, 2016; Lefèvre, Lundqvist, Drevenhorn, & Hallström, 2015, 2016). The leaders act as experts and lecturers, and not as moderators to facilitate discussion and interaction between the parents (Berlin et al., 2018; Berlin et al, 2016; Forslund Frykedal & Rosander, 2015; Hoddinott, Allan, Avenell, & Britten, 2010; Lefèvre, Lundqvist, Drevenhorn, & Hallström, 2014), which is what many parents want (Berlin et al., 2018, Berlin, Rosander, Forslund Frykedal & Barimani, in review; Forslund Frykedal, Rosander, Barimani, & Berlin, 2019; Forslund Frykedal & Rosander, 2015; Ho & Holroyd, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…However, group leaders express feelings that they do not have enough pedagogical knowledge to lead PE groups (Barlow, Redshaw, & Underdown, 2009; Berlin, Rosander, Forslund Frykedal, & Barimani, 2018; Forslund Frykedal, Barimani, Rosander, & Berlin, 2019; Forslund Frykedal, Rosander, Berlin, & Barimani, 2016; Lefèvre, Lundqvist, Drevenhorn, & Hallström, 2015, 2016). The leaders act as experts and lecturers, and not as moderators to facilitate discussion and interaction between the parents (Berlin et al., 2018; Berlin et al, 2016; Forslund Frykedal & Rosander, 2015; Hoddinott, Allan, Avenell, & Britten, 2010; Lefèvre, Lundqvist, Drevenhorn, & Hallström, 2014), which is what many parents want (Berlin et al., 2018, Berlin, Rosander, Forslund Frykedal & Barimani, in review; Forslund Frykedal, Rosander, Barimani, & Berlin, 2019; Forslund Frykedal & Rosander, 2015; Ho & Holroyd, 2002). The goals for the PE groups are to support parents in the transition to parenthood, increase knowledge about child development and co‐parenting relationships and help parents to develop social networks (National Handbook of Child Health Services, 2019; SOU, 2008).…”
Section: Introductionmentioning
confidence: 99%